Building with graphene oxide: effect of graphite nature and oxidation methods on the graphene assembly. Issue 6 (18th January 2021) - Kim, Ji Hoon; Shim, Gyu Hyeon; Vo, Thi To Nguyen; Kweon, Boyeon; Kim, Koung Moon; Ahn, Ho Seon
Abstract : In this study, the article investigated the effect of starting graphite sources, and oxidation methods on graphene oxide (GO) synthesis and the porous structure of building assembly into thermally expanded graphene oxide (TEGO). Abstract : During nearly 2 centuries of history in graphene researches, numerous researches were reported to synthesize graphene oxide (GO) and build a proper graphene assembly. However, tons of research prevail without verifying the reproducibility of GO that can be sensitively attributed by the graphite nature, and chemical processes. Here, the structure and chemistry of GO products were analyzed by considering parent graphite sources, and three different oxidation methods based on Hummer's method and the addition of H3 PO4 . The oxidation level of GO was characterized by monitoring the C/O and sp 2 carbon ratio from X-ray photoelectroscopy (XPS) spectra. It was observed that the oxidant intercalation behavior was dependent on the morphological differences of graphite; synthetic and natural flake graphite were compared based on their origins in shape and size from different suppliers. Thermal reduction and exfoliation were applied to GO powders to prepare thermally expanded graphene oxide (TEGO) as a graphene assembly. Gas releases from the reduction of oxygen functional groups split layered GO structure and build a porous structure that varied specific surface area regarding oxidation degrees of GO.